KEBIJAKAN PEMERINTAH DAERAH TERHADAP TEMPAT TINGGAL SUKU ANAK DALAM PADA PERUMAHAN MADANI DI DESA LUBUK JERING KECAMATAN AIR HITAM KABUPATEN SAROLANGUNG - Parwanida; Budi Juliardi; Indra Rahmat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the Sarolangun Regency Government's policy regarding the housing of the Suku Anak Dalam (SAD) through the Madani Housing program in Lubuk Jering Village, Air Hitam District. The research focuses on the social impact of this policy on the lives of the SAD and the extent of their participation in the decision-making process. This study used a qualitative approach with descriptive methods, and data collection techniques included observation, in-depth interviews, and documentation. The results indicate that the policy of relocating the SAD to Madani Housing has had a positive impact in terms of providing physical facilities, but it is not fully aligned with the SAD's nomadic culture and lifestyle. Furthermore, SAD community participation in the decision-making process remains low due to limited communication and a lack of cultural understanding on the part of the government. This lack of participation has led to internal conflict within the SAD community and hindered their adaptation to their new environment. This study recommends the need for a more participatory approach based on local wisdom in formulating policies related to indigenous communities such as the SAD.